PERUBAHAN SISTEM MEKANISME PASAR GROSIR MODERN DAYA UNTUK UNTUK MENARIK MINAT PELAKU PASAR - Utami, Wiji; Amelia, Rezki; Mutmainnah, Mutmainnah (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2014)
The change system of Daya Modern Wholesale market Mechanism is necessary because the system in place does not run propertly in accordance with. Associated with the existing system, the less the saller Latituted in marketing various kinds of merchandise, numer of trade sale price competation, the high prince of rent stalls/ kiosk, so in need of more serious treatment. That’s what limits the interes of traders in traditional markets to modern reluctant to sell in the market that had been prepared. In this study, discussion or research methods used there are 3 ways to market directly to the site observation, the survey by interviewing the traders and buyers in the market as well as distributing questionarto the merchant in order to confirm the results of research. From the research that have has been done the result is permanent traders selling in the market traditional and modern markets that have been built are not working prorely. So that the conclutions and recommendations that can be given is to change the system of Daya Modern Wholesale Market mechanisms to attract market participants.